Dietary Sutherlandia and Elderberry Mitigate Cerebral Ischemia-Induced Neuronal Damage and Attenuate p47phox and Phospho-ERK1/2 Expression in Microglial Cells. (9th October 2014) - Chuang, Dennis Y.; Cui, Jiankun; Simonyi, Agnes; Engel, Victoria A.; Chen, Shanyan; Fritsche, Kevin L.; Thomas, Andrew L.; Applequist, Wendy L.; Folk, William R.; Lubahn, Dennis B.; Sun, Albert Y.; Sun, Grace Y.; et al.
Sutherlandia ( Sutherlandia frutescens ) and elderberry ( Sambucus spp.) are used to promote health and for treatment of a number of ailments. Although studies with cultured cells have demonstrated antioxidative and anti-inflammatory properties of these botanicals, little is known about their ability to mitigate brain injury. In this study, C57BL/6 J male mice were fed AIN93G diets without or with Sutherlandia or American elderberry for 2 months prior to a 30-min global cerebral ischemia induced by occlusion of the bilateral common carotid arteries (BCCAs), followed by reperfusion for 3 days. Accelerating rotarod assessment at 24 h after BCCA occlusion showed amelioration of sensorimotor impairment in the mice fed the supplemented diets as compared with the ischemic mice fed the control diet. Quantitative digital pathology assessment of brain slides stained with cresyl violet at 3 days after ischemia/reperfusion (I/R) revealed significant reduction in neuronal cell death in both dietary groups. Immunohistochemical staining for ionized calcium-binding adapter molecule-1 demonstrated pronounced activation of microglia in the hippocampus and striatum in the ischemic brains 3 days after I/R, and microglial activation was significantly reduced in animals fed supplemented diets. Mitigation of microglial activation by the supplements was further supported by the decrease in expression of p47phox, a cytosolic subunit of NADPH oxidase, and phospho-ERK1/2, a mitogen-activated protein kinase known to mediate a number of cytoplasmic processes including oxidative stress and neuroinflammatory responses. These results demonstrate neuroprotective effect of Sutherlandia and American elderberry botanicals against oxidative and inflammatory responses to cerebral I/R.